O setor serviços no Brasil - Pereira, Vinicius Rena [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation investigates the tertiarisation of the Brazilian economy, between 2000 and 2009, from the productive structure. Also evaluates if the increase in the deficit of the balance of services in the recent period (2005-2013) is conjunctural or structural, identifying productive activities responsible for the deterioration and linking to the ability to induce economic growth. The methodology was based on the calculation from the input-output matrix, the multipliers of production and employment; the levels of Hirschman-Rasmussen intersectoral relations and intersectoral connection indices pure in GHS methodology. The paper concludes that the tertiarisation of the Brazilian economy has centralized in activity with low wages, multipliers and rates of intersectoral relationship while the deficit of the balance of services has centralized in activities with exactly opposite characteristics

Esta dissertação investiga a terciarização da economia brasileira, entre 2000 e 2009, pela da ótica de sua estrutura produtiva. Além disso, também avalia se o agravamento do déficit da balança de serviços no período recente (2005 - 2013) é conjuntural ou estrutural, identificando as atividades produtivas responsáveis pela deterioração da balança e as relacionando com a capacidade de induzir o crescimento econômico. A metodologia utilizada baseia-se nos cálculos, a partir da matriz insumo-produto, dos multiplicadores de produção e emprego; dos índices de relações intersetoriais de Hirschman-Rasmussem e dos índices de ligação intersetorial puros na metodologia GHS. O trabalho conclui que a terciarização da economia brasileira está centrada em atividade com baixos salários, multiplicadores e índices de relação intersetorial; ao passo que o déficit da balança de serviços, em atividades com características opostas
Keywords: Economia - Brasil; Fatores socioeconômicos - Brasil; Relações intersetoriais - Brasil; Economics